(untitled) (Journal of University of Babylon for Engineering Sciences, 2023)
This research investigates experimentally the reduction of gases emitted from a plane concrete frame by reducing the amount of concrete due to the use of non-prismatic cross-sections. The study includes casting three frames using normal-strength concrete. Two plane frames with non-prismatic cross-sections of the columns and beam and one frame with prismatic cross-sections. The amount of concrete used for all three specimens is the same. The frame was tested under static load by two concentrated loads on the beam. The results showed that the use of non-prismatic sections improves the performance of the concrete frame and increases the load capacity of the frame in the same amount of concrete, so the cost of the project and the gases emitted can be reduced through the use of non-prismatic sections. The ultimate load of the non-prismatic concrete frame with columns and beam increases by 25% and 16%, respectively. Using non-prismatic sections decreases the frame’s stiffness (at beam and columns) and using non-prismatic sections in the beam, the frame’s shear failure is improved and less fragile than the prismatic sectional frame.